Assessment of losses caused by Peronosclerospora heteropogoni, incitant of downy mildew of Maize - and KUSUM MATHUR, AMIT TRIVEDI*, R.S. RATHORE (Indian Phytopathology, 2006)
Among biotic constraints, Rajasthan downy mildew (RDM) (Peronosclerospora heteropogoni) is a major disease limiting the maize yield potential in the state. At the infection of 67.9% losses were 35.5% compared to protected (seed treated) plots in susceptible cv. Kiran. Resistant cultivar Prabhat also developed low level of RDM (13.5%) that resulted in 6.5% loss in grain yield as compared to the plots raised with fungicides treated seeds. For effective management of RDM, integration of host plant resistance (HPR) and fungicidal seed treatment seems promising.